2
$\begingroup$

I am wondering how one would go about constructing a "only one" statement using first order logic.

I stumbled into an example that said "Only one student took Greek in Spring of 2011."

I can easily construct something like "There is a student who took Greek in Spring of 2011." How can I add "Only one" to it?

$\endgroup$
3
  • 1
    $\begingroup$ Hint: What can be said about any $x$ and $y$ such that each took Greek? $\endgroup$ Mar 30, 2017 at 12:18
  • 2
    $\begingroup$ Roughly you want to say that there exists an element with that property, and for any element different from that element, the property does not hold. $\endgroup$
    – mrp
    Mar 30, 2017 at 12:19
  • $\begingroup$ @MaliceVidrine I see! We say that they are equal? $\endgroup$ Mar 30, 2017 at 12:21

4 Answers 4

9
$\begingroup$

The usual way is to say that if two elements both satisfy the property, then they are the same element.

In other words, the sentence

There exists exactly one $x$ such that $P(x)$

is written as

$$\exists x: (P(x)\land \forall y:(P(y)\implies x=y))$$

$\endgroup$
2
$\begingroup$

$$\exists x\forall y: P(y) \Leftrightarrow x=y$$

This means especially that $\exists x: P(x)\Leftrightarrow x=x$, or $\exists x: P(x)$. Also it implies that if $P(x)$ and $P(y)$ we have that $x=y$.

$\endgroup$
1
  • $\begingroup$ @lemontree I've completely reformulated the answer... $\endgroup$
    – skyking
    Mar 30, 2017 at 13:23
1
$\begingroup$

$(\exists x)(f(x) \land (\forall y)(f(y)\rightarrow y=x))$, where $f$ means "having taken Greek."

$\endgroup$
1
$\begingroup$

The idea is to express the uniqueness condition by means of identity between entities to which the property in question applies.
This amounts to stating that "$x$ has the property $P$, and all entities which also have property $P$ must be identical to that very $x$" or, slightly differently worded, "$x$ has the property $P$, and there is no other entity which also has the property $P$ and is different from $x$".

Formally, this can be expressed as

$\exists x (P(x) \land \forall y (P(y) \to x = y))$

or

$\exists x (P(x) \land \neg \exists y (P(y) \land x \neq y))$

It can easily be shown that the two formulations are equivalent in their truth conditions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.